Increased Expression of Dopamine Receptors in Synovial Fibroblasts From Patients With Rheumatoid Arthritis: Inhibitory Effects of Dopamine on Interleukin‐8 and Interleukin‐6. Issue 10 (October 2014) - Capellino, Silvia; Cosentino, Marco; Luini, Alessandra; Bombelli, Raffaella; Lowin, Torsten; Cutolo, Maurizio; Marino, Franca; Straub, Rainer H.
<x xml:space="preserve">Abstract</x> Objective Observations in both animal models of arthritis and patients with rheumatoid arthritis (RA) suggest a role for dopamine and its receptors in RA. Because synovial fibroblasts (SFs) contribute to inflammation and joint destruction in RA, the aim of this study was to investigate dopaminergic pathways in SFs obtained from patients with RA and, for comparison, in SFs from patients with osteoarthritis (OA) undergoing knee joint replacement surgery. Methods The expression of all dopamine receptors (D1–D5) and dopamine transporter was assessed by immunofluorescence and immunohistochemical staining. The levels of dopamine receptor and tyrosine hydroxylase messenger RNA were measured by real‐time polymerase chain reaction. The intracellular content of dopamine, its precursor, and its main metabolites was assayed by high‐performance liquid chromatography. The influence of dopamine on proinflammatory interleukin‐6 (IL‐6) and IL‐8, matrix metalloproteinase 3, and tissue inhibitor of metalloproteinases 1 (TIMP‐1) and TIMP‐2 was studied in SFs. Results SFs possess an intrinsic dopaminergic system, including dopamine receptors, dopamine transporter, and tyrosine hydroxylase, and contain dopamine, its precursor, and its main metabolites. SFs from patients with RA, in comparison with those from patients with OA, showed increased expression of dopamine receptors D1 and D5, and exogenous dopamine strongly inhibited the production of IL‐8 in patients with RA. Conclusion SFs from patients with RA and patients with OA show a dopaminergic phenotype. The expression of D1‐like dopamine receptors was higher in RASFs, and this increased expression may lead to antiinflammatory effects, as demonstrated by the expression of IL‐8. Studies in animal models and patients with RA are needed to assess the therapeutic potential of endogenous, local production of dopamine in synoviocytes.